Transplanted Endothelial Progenitor Cells Improve Ischemia Muscle Regeneration in Mice by Diffusion Tensor MR Imaging - Xin-Gui Peng; Yingying Bai; Judy R. James; Darya P. Shlapak; Shenghong Ju (Stem Cells International)
Endothelial progenitor cells (EPCs) play an important role in repairing ischemia tissues. Diffusion tensor imaging (DTI) was applied to detect the architectural organization of skeletal muscle. This study investigated the feasibility and accuracy of using the DTI to evaluate effectiveness of EPCs treatment. Mouse bone marrow-derived EPCs were isolated, cultured, characterized, and transplanted to hindlimb ischemia mice model. DTI was performed on the hindlimb at postischemia time points. The edema regions of diffusion restriction (high signal in diffusion weighted imaging) were decreased in the ischemic muscle of EPCs treated mice after 14 days compared with the controls. These results from DTI show the lower apparent diffusion coefficient and eigenvalues (λ1, λ2, and λ3) and the higher fractional anisotropy and fiber counts of ischemic muscle on 7 and 14 days after EPCs treatment compared to the controls. There was a significant correlation between fiber counts calculated by DTI and survival fibers evaluated by histological section (r=0.873, P<0.01). Our study demonstrated that the time frame for muscle fiber regeneration after EPCs transplantation was significantly shortened in vivo. DTI could be a useful tool for noninvasive evaluation of muscle tissue damage and repair in animal models and patient with ischemic diseases.